LITERASI NUMERASI DALAM PEMBELAJARAN TEMATIK SISWA KELAS 3 SD/MI - Maya Nurjanah; Diah Tara Dewi; Kukuh Maulana Al Fathan; Intan Dewi Mawardini (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
The purpose of the study was to describe numeration literates in integrated thematic study in a bandung class of 3 mi al-rasyidiyah. The approach in this research is a descriptive culinary. This research conducted a data collection with an interview technique for a 3rd grade teacher - rasyidiyah, test sheets and documentation. Test sheets are composed of several numerical literations about weight-unit matter. The conclusion based on the discussion was the ability of 3rd graders in mi al-rasyidiyah the city of bandung in dealing with numeration literacy was said to be good enough, but more care is required when understanding the content of a story text in the problem and the student's ability when doing solutions on numeration literacy needs to be enhanced again